Administrative Resistance In Child Marriage And Sustainable Islamic Family Law - Fitriana (Journal of Islamic Economic and Law (JIEL), 2026)
Child marriage remains a socio-legal issue in the implementation of child protection and sustainable Islamic family law. This study aims to analyze the practice of administrative resistance in child marriage and its implications for the implementation of sustainable Islamic family law and Target 5.3 of the Sustainable Development Goals. This study employs an empirical legal research design with descriptive-analytical specifications using a qualitative approach within a socio-legal paradigm through in-depth interviews, observation, and document analysis. The findings reveal that child marriage continues through the adaptation between socio-religious practices and formal legal procedures, particularly through marriage dispensation, unregistered marriages, and post-marriage administrative legalization. These findings indicate a gap between the normative objectives of legal reform and social realities within society. Therefore, preventing child marriage requires the integration of child protection, education, gender equality, and the transformation of socio-religious authority.